An assessment of nitrogen loading and biogas production from Italian livestock: A multilevel and spatial analysis. (1st October 2021) - Ferrari, Giovanni; Ai, Ping; Alengebawy, Ahmed; Marinello, Francesco; Pezzuolo, Andrea
Abstract: The management of livestock effluents to reduce their environmental impact requires knowledge of not only the quantity produced but also the availability of agricultural areas, the condition of contiguous areas and the opportunity to exploit the energetic value of effluents. In this paper, a description of the Italian livestock system is provided, with a focus on its consequences in terms of the nitrogen load and biogas potential produced by the management of effluents. The analysis considered 9, 589 million animal units (AU) and indicated an overall nitrogen production of 508 × 10 6 tons, while the methane potential can reach 1, 764 × 10 6 m 3, equal to 6.1% of the national electric energy consumption. To organize effective collection and treatment of effluents, their spatial distribution was investigated using spatial statistical tools: Moran's index and local indicator of spatial association (LISA). Moran's index analysis showed that animal units (Moran's I = 0.63), nitrogen load per hectare of UAA (Moran's I = 0.35) and methane potential per square kilometre (Moran's I = 0.58) were significantly clustered. Using LISA, a series of maps and scatter plots were elaborated to identify clusters of high nitrogen loads and high methane production. The analysis showed that 764 municipalities are included in clusters of a high density of livestock, and 635 municipalities resulted in clusters of high methane potential. The results demonstrated the robustness of these instruments to evaluate the presence of nitrogen/biogas production clusters and the possibility of combining the treatment of nitrogen and the production of biogas from animal effluents. Analysing the distribution of livestock and the 2, 723 biogas plants operating in Italy, the study found that 75.0% of the bioresources are available 5 km from the nearest biogas plant, 89.9% at 10 km, 94.7% at 15 km and 97.4% at 20 km.